Perspectives on Colon Cancer Screening-A Physician Panel Discussion for Preclinical Medical Students - Christen K. Dilly; Hannah J. Craven; Jean P. Molleston (Association of American Medical Colleges, 2020)
Introduction Colon cancer is the third most common cancer in the US, and the survival rate improves drastically with early detection. It is important for medical students to understand screening options, and to be able to effectively discuss these options with their patients. While basic information about colon cancer screening is ubiquitous in US medical school curricula, no published curricula describe teaching students the nuances of negotiating this discussion with patients and tailoring screening to individual patients' needs. Methods We developed a 90-minute session for second-year medical students as part of a gastroenterology and nutrition course. We provided a short lecture on colon cancer screening. We then had a panel of practicing gastroenterologists and a primary care physician discuss their approaches to six hypothetical cases. The students reflected in writing on what they learned from the session and on their opinions of the session format. Results Of second-year medical students, 139 attended the session and 110 submitted written reflections on the session (79% response rate). The students perceived significant gains in knowledge, communication skills, and attitudes around the discussions. Discussion This expert panel session taught medical students knowledge and communication skills related to colon cancer screening. The session could be easily implemented at any medical school, either at the preclinical or clinical level.